A comparative study on the oxidation behaviours of a TNM alloy in argon and oxygen atmospheres at 650 °C. (June 2021) - Shaaban, Ali; Hayashi, Shigenari; Takeyama, Masao
Highlights: Oxide scales of similar structures but different growth kinetics formed on TNM alloy at 650 °C in Ar and O2 . TiNb2 O7 and AlNbO4 may slow the oxidation kinetics of TNM alloy at 650 °C in Ar. Amorphous Al2 O3 without Ti(Al)N formation did not sufficiently slow the oxidation kinetics of TNM alloy at 650 °C. The TNM alloy's oxidation behaviour is not greatly dependent on the oxygen level. A nitride layer and β-stabilizers enrichment influenced the TNM alloy's oxidation kinetics. Abstract: This study investigated the oxidation behaviours of a TiAl (TNM) alloy oxidized at 650 °C in argon and oxygen. The oxidation mass gains were similar in both atmospheres up to 200 h of oxidation. Between 200 and 500 h, the mass gains increased by 20 % in the O2 atmosphere. This study examined the triplex oxide scales of outer (Ti–Al)O layer-by-layer and Mo/Nb-rich TiAl oxides on the TNM alloy after oxidation in Ar and O2 . The scale structures formed in Ar and O2 were similar but differed from those formed in air, and the respective TNM samples' oxidation behaviours were different.